A quantitative review on outcome-to-antidepressants in melancholic unipolar depression. (July 2018) - Valerio, Marina P.; Szmulewicz, Alejandro G.; Martino, Diego J.
Highlights: Melancholic unipolar depression may have lower odds of remission to antidepressants. A higher differential response rate drug/placebo could be observed in melancholia. Patients with melancholia could achieve better outcome with tricyclic antidepressants. Due to scarce data available and other limitations the results are preliminary. Abstract: The aim of this study was to explore outcome to antidepressants profile in melancholic unipolar depression. We conducted a systematic review of electronic databases and meta-analysis of randomized and nonrandomized trials comparing: 1) outcome to antidepressants and placebo between melancholic and non-melancholic depression; 2) outcome to different antidepressant classes in melancholic depression. Two outcomes were considered: clinical remission and response. Significant lower odds of remission to antidepressants in melancholic than in non-melancholic depressions were found. Although no significant differences were observed in the response to antidepressants between both subtypes of depression, those with melancholic features had lower odds of response to placebo. Finally, treatment of melancholic depression with serotonin reuptake inhibitors was associated with lower odds of remission compared with tricyclic antidepressants, and similar outcome compared with venlafaxine. Melancholia seems to show a differential pattern of outcome to antidepressants, which could be clinically valuable for a better implementation of personalized medicine of depression. Due to several limitations, further research is needed to support these preliminary findings.